1960
DOI: 10.1136/thx.15.3.204
|View full text |Cite
|
Sign up to set email alerts
|

A Report of 12 Selected Cases of Pulmonary Histoplasmosis

Abstract: Once considered a rare and fatal disease, histoplasmosis is now increasingly suspected or diagnosed. There may be two apparent reasons for this; first, it is possible that pulmonary histoplasmosis has always been prevalent, but increase in knowledge and modern diagnostic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1962
1962
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Following this the number of cases has been increasing in most countries in the world. 5 The first histoplasmosis survey was done in Bangladesh in 1961 (then East Pakistan), which revealed that 12-23% of people had a positive skin reaction to histoplasmin. 6 The first case of histoplasmosis was reported1982 in Bangladesh 7 and the second case in 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Following this the number of cases has been increasing in most countries in the world. 5 The first histoplasmosis survey was done in Bangladesh in 1961 (then East Pakistan), which revealed that 12-23% of people had a positive skin reaction to histoplasmin. 6 The first case of histoplasmosis was reported1982 in Bangladesh 7 and the second case in 2005.…”
Section: Discussionmentioning
confidence: 99%